Frequency of Smoking Cessation Following Acute Coronary Syndrome: A Review of Effective Counselling - Hidayatullah, .; Abidullah, .; Ayaz, Shama; Ullah, Safi; Mal, Kheraj; Aamir, Muhammad (Biological and Clinical Sciences Research Journal, 2025)
Acute coronary syndrome (ACS) is known to be among the most prevalent causes of mortality and is particularly worsened by smoking. Optimally designed and implemented cessation interventions in the following days or weeks after the first ACS event are warranted in Pakistan, where tobacco use remains pervasive. Objective: To evaluate the frequency of smoking cessation post-ACS in patients undergoing percutaneous coronary intervention (PCI) and assess the effectiveness of pre-discharge counseling in Khyber Pakhtunkhwa, Pakistan. Methods: This cross-sectional study was conducted on 200 patients of ACS presenting for PCI at MTI-Peshawar Institute of Cardiology in the duration from July, 2024 to December, 2024. All patients reported pre-discharge counseling for cessation, and their cessation was reinforced at 1, 3, and 6 months. Results: Among 200 patients 46% quit tobacco at 6 months, quit rates were higher among educated 60% and professional 55%. Frequency of use (44%) was attributed to cultures and psychological factors. Conclusion: Pre-discharge counseling achieved moderate cessation success, but sustained interventions are needed to address regional challenges and improve outcomes.